Lycium barbarum L. and Salvia miltiorrhiza Bunge protect retinal pigment epithelial cells through endoplasmic reticulum stress. (5th October 2022) - Ou, Chen; Xie, Wei; Jiang, Pengfei; Wang, Ying; Peng, Jun; Zhou, Yasha; Song, Houpan; Peng, Qinghua
Abstract: Ethnopharmacological relevance: Lycium barbarum L. and Salvia miltiorrhiza Bunge (Gouqi and Danshen, LS) are traditional herbs for the treatment of retinal degeneration in China. LS have been integrated into pharmacopoeia and health care system of many countries around the world. However, the mechanisms by which LS protect retina are not fully clarified. Aim of the study: We aimed at exploration of the effect of LS on retinal pigment epithelium (RPE) cells apoptosis as well as the endoplasmic reticulum (ER) stress mechanisms. Material and methods: ARPE-19 cells were exposed to tunicamycin to induce ER stress, followed by LS treatment for 24 h. The cell morphology was photographed using the Incucyte S3 instrument, and the potential cytotoxic effect and viability were evaluated by CCK-8 assays. The Annexin V-FITC/PI staining and TUNEL assay were conducted to detect cells apoptotic. Western blot and digital PCR were used to detected related protein and gene expression. Results: The ARPE-19 cells are increased in number and aligned after treating with LS. 1 mg/ml is the LS high dose group dose and treatment with LS increased cell vitality. LS significantly inhibit ARPE-19 cells apoptosis. Moreover, LS were markedly decreased the expression levels of ER stress-related factors in the ARPE-19 cells. Conclusions: This study reveals that LS relieve ARPE-19 cells apoptosis by inhibiting ER stress, and here we can speculate that LS have a certain protective effect on retina. Graphical abstract: Image 1 Highlights: Lycium barbarum L. and Salvia miltiorrhiza Bunge against tunicamycin-induced endoplasmic reticulum stress cell model was first explored.